The Obscene Coupling Known as Spaghetti Code: Teach your junior programmers how to read code. - Neville-Neil, George V. (Communications of the ACM, 2018)
The article offers an answer to a question about teaching computer programming in relation to avoiding coding known as spaghetti code, noting the importance of communication in programming.